An analysis of migrant workers from the Northern Ireland Census : A detailed analysis of the sectors, skills, occupations and location of migrant workers in Northern Ireland from the 2011 Census.: A detailed analysis of the sectors, skills, occupations and location of migrant workers in Northern Ireland from the 2011 Census. (2018) - Northern Ireland., Department for the Economy., EU Exit Analysis Branch,
No abstract available